A Lookup Table Model Predictive Direct Torque Control of Permanent-Magnet Synchronous Generator Based on Vienna Rectifier - Yip, Sook Yee; Che, Hang Seng; Tan, Chee Pin; Chong, Wen Tong (Institute of Electrical and Electronics Engineers, 2020)
This paper presents the development and implementation of a lookup table model predictive direct torque control (LUT-MPDTC) for a permanent-magnet synchronous generator controlled using a Vienna rectifier. Using a machine model in the stator synchronous reference frame, the feasibility of direct torque control-based model predictive control for the Vienna rectifier is demonstrated. To reduce the computational burden of the MPDTC, a lookup table (LUT) is proposed based on the stator current position and dc-link voltages. The LUT simplifies the complexity of the MPDTC by reducing the number of switching vectors from eight to five, while maintaining the stabilization of the neutral point voltage. The performance and effectiveness of the proposed method are evaluated via MATLAB/Simulink and further validated experimentally using a Texas Instrument-based TMS320F28335 development board. The simulation and experimental results show that the proposed LUT-MPDTC can successfully improve the torque and stator flux ripples as compared to the classical DTC. © 2013 IEEE.